2013
DOI: 10.1099/vir.0.046862-0
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic diversity and seroprevalences of Torque teno viruses in children and adults by ORF2-based immunoassays

Abstract: Torque teno viruses (TTVs) circulate widely among humans, causing persistent viraemia in healthy individuals. Numerous TTV isolates with high genetic variability have been identified and segregated into 29 species of five major phylogenetic groups. To date, the diversity of TTV sequences, challenges in protein expression and the subsequent lack of serological assays have hampered TTV seroprevalence studies. Moreover, the antigenic relationships of different TTVs and their specific seroprevalences in humans rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
0
20
0
2
Order By: Relevance
“…Anelloviruses are under immunological control, since induced or inborn immunodeficiency is associated with increases in viral loads (59)(60)(61)(62)(63). The rates of seroreactivity were shown to increase rapidly in infants (64), and infection is believed to be generally chronic. Anelloviruses have been reported in many tissues and bodily fluids, including respiratory fluids, blood, breast milk, cervical secretions, semen, urine, and feces (65)(66)(67)(68)(69)(70)(71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%
“…Anelloviruses are under immunological control, since induced or inborn immunodeficiency is associated with increases in viral loads (59)(60)(61)(62)(63). The rates of seroreactivity were shown to increase rapidly in infants (64), and infection is believed to be generally chronic. Anelloviruses have been reported in many tissues and bodily fluids, including respiratory fluids, blood, breast milk, cervical secretions, semen, urine, and feces (65)(66)(67)(68)(69)(70)(71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, ORF2 region encodes a protein of near about 20 KDa [8] which is a non-structural protein and has been reported to induce host immune response against TTV [8,[34][35][36]. Although, earlier attempts in several studies focused on the expression of N22 region [26] and ORF1 [28,37], however, their protein product could not prove successful antigenic agent to induce host immune response or for their use in developing immunoassays for sero-detection of TTV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although similar attempts were made in the past using various subgenomic regions of TTV-DNA, including ORF-1 [40,43,44] and ORF-2 [15,28,32]; however, we envisaged that N22, being a conserved region, could be a better subgenomic region for use in the development of immunoassay. Furthermore, all of the studies reported so far are based on genotype 1 since it is highly prevalent globally.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have demonstrated that different genetic variants are antigenically distinct. However, it is not clear whether these variants have some biological or pathogenic differences also [15]. Of course, few recent reports point to an association between genotypes/genogroups and the type of disease caused [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation